Standardization of tree architectural techniques for higher apple productivity on dwarfing rootstock (Current Horticulture, 2024)
There was a significant and positive correlation between yield and Trunk cross Sectional Area (TCSA). Consistently high productivity (16.7, 52.29, 96.05, 102.35 and 61.84 t/ha) with medium-sized and large number of fruits were recorded in Coe Red Fuji, and minimum (6.0, 30.72, 22.28, 86.45 and 58.01 t/ha) in Spartan during 2011-13. The TCSA is reliable criteria to estimate tree vigor, crop load and yield efficiency, maximum TCSA (25.99, 27.90, 33.31, 37.02 and 38.83) over the years were noted in Coe Red Fuji. The TCSA has positive correlation with fruit weight and yield efficiency. Maximum mean yield efficiency (1.11 kg/cm2) was recorded in Granny Smith. High chroma (color intensity) observed in all varieties on espalier architecture.
Keywords: Architectural techniques; Espalier; Granny Smith; Coe- Red Fuji; Trunk cross sectional area; Yield efficiency